High frequency of seropositive and carriers of Leptospira spp. in pigs in the semiarid region of northeastern Brazil - Fernandes, Juciê Jales; Araújo Júnior, João Pessoa [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; da Costa, Diego Figueiredo; Silva, Maria Luana Cristiny Rodrigues; Alves, Clebert José; de Azevedo, Sergio Santos; Higino, Severino Silvano dos Santos (Springer Nature, 2020)
Carrier animals are considered key in the transmission cycle of leptospirosis. Although investigations have been carried out on several species, the role of pigs in the epidemiology of the disease is still poorly studied in the semi-arid region. Thus, the objective of this study was to determine the presence of Leptospira spp. in the genitourinary tract of pigs intended for slaughter. Fifty pigs were used: adults and unvaccinated. Samples of the kidney, urine, and vaginal fluid were collected for the molecular detection of Leptospira spp. and blood samples for the serological test. The molecular test was performed using the polymerase chain reaction (PCR), and the serological test was performed with the microscopic agglutination test (MAT). Samples with DNA amplification were submitted to genetic sequencing. Twenty (40%) animals were found with anti-Leptospira spp. antibodies, and the majority of the reactions (50%) occurred for the serogroup Tarassovi. Leptospiral DNA was found in the tissue of 11 (22%) pigs. The gene from a urine sample was sequenced and showed similarity to L. borgpetersenii. The results evidenced a high rate of porcine carriers; therefore, they appear to be important sources of agent infection, being potential transmitters of the disease to other animal species and man.
Keywords: Genital carriers; Leptospirosis; Pigs; Slaughterhouses